POTENTIALITY OF CO-BENEFITS OF CLIMATE AND AIR QUALITY IN FUEL SWITCHING FOR HANOI BUS SYSTEM - Trang, Nguyen Thu; Dung, Nghiem Trung; Trang, Tran Thu (Vietnam Journal of Science and Technology, 2012)
Potentiality of co-benefits of climate and air quality in fuel switching from diesel to CNG (compressed natural gas) or LPG (liquefied petroleum gas) for Hanoi bus system was studied. Three areas and two bus routes in Hanoi were selected for conducting this study. Information of technical conditions of the bus system was collected by 100 questionnaires at 5 bus stations in Hanoi. Traffic flow was determined by vehicle counting in 9 different roads/streets. Real-time information on driving behavior of 2 bus routes was obtained by GPS. All data collected were processed to generate input files to run IVE model (international vehicle emission model) with base state and 4 scenarios. Emission factors (EFs) of Hanoi bus system and the reduction of CO2 equivalent for each scenario were determined. Results indicate that fuel switching from diesel to CNG obtains the better improvement of air quality while changing from diesel to LPG achieves better contribution to climate change mitigation. At base state, EFs of CO, VOC, NOx, SO2, PM, CO2 and N2O for Hanoi bus system are in the same range with those in other cities having the similar traffic conditions in the world.